A study of prevalence of tobacco use and related factors among medical students as per the Global Health Professions Student Survey protocol - Brar, Manmohan; Chaudhary, Neha; Ramakrishnan, T. S.; Randhawa, Avneet (International Journal of Research in Medical Sciences, 2020)
Background: Physicians who smoke are less likely to ask patients about their smoking and initiate cessation interventions. Hence it is important to study the prevalence of tobacco use, attitude and training of health professional students. Objectives were to study prevalence and attitudes towards tobacco use and training related to tobacco cessation. Methods: Armed Forces Medical college-based cross-sectional survey by anonymous, self-administered questionnaire as per Global Health Professions Student Survey (GHPSS) was conducted. Data was compiled and analyzed for various variables as per the GHPSS questionnaire. Results: Forty-two percent of the students had ever smoked cigarettes and 24% were current smokers. Nearly one in five had tried their first cigarette before 20 years of age. Male gender was associated with smoking. There is a significant association between not smoking and support for smoking ban in public places. Almost all the respondents (98.1%) thought smoking should be banned in all enclosed public places. In light of 20.6% of all respondents who smoked in college buildings during past this year indicated a gap between their knowledge, attitude and behavior. There was a strong desire to quit smoking but only 42% reported receiving help/ advice to stop smoking. Only one in ten reported receiving formal training in smoking cessation techniques. Conclusions: The fight against tobacco can get a boost through interventions aimed at health care professional students. Active Interventions should be made to address smoking issues among medical students. Skill based medical school curriculum should incorporate and emphasize on acquiring effective smoking cessation skills.